Preparation of Idebenone as a Thermosetting Nasal Gel for Better Bioavailability and Histopathological Effect - Hussein Jaafer; Khalid Kadhem Al-Kinani (مجلة كلية الطب, 2023)
Background Idebenone is an extensively metabolized drug with poor water solubility that is used to treat Leiber’s hereditary optical neuropathy.